How is paediatric chronic fatigue syndrome/myalgic encephalomyelitis diagnosed and managed by paediatricians? An Australian Paediatric Research Network Study. (10th July 2014) - Knight, Sarah; Harvey, Adrienne; Towns, Susan; Payne, Donald; Lubitz, Lionel; Rowe, Kathy; Reveley, Colette; Hennel, Sabine; Hiscock, Harriet; Scheinberg, Adam
<x xml:space="preserve">Abstract</x> Aim The diagnosis and management of paediatric chronic fatigue syndrome/myalgic encepnalomyelitis (CFS/ME) represent ongoing challenges for paediatricians. A better understanding of current approaches at a national level is important in informing where research and education could improve treatment outcomes. We aimed to examine current diagnosis and management practices for CFS/ME by Australian paediatricians. Method An online survey was sent to members of the Australian Paediatric Research Network. The primary outcomes of interest included diagnostic criteria used, medical investigations and management practices in paediatric CFS/ME. Results One hundred seventy‐eight (41%) of 430 eligible paediatricians responded, with 70 of the 178 (39%) reporting that they diagnose and manage CFS/ME as part of their practice. Medical investigations used for diagnosis were variable. Conditions that more than half of the paediatricians reported as commonly co‐occurring (i.e. present in >50% of cases) included somatisation disorders, anxiety, depression and fibromyalgia. There was wide variation in behavioural and pharmacological management strategies but most paediatricians commonly engaged a school teacher, physiotherapist and/or psychologist as part of their management. Conclusion The diagnostic and management practices of paediatricians for CFS/ME within Australia vary widely. This likely reflects a paucity of paediatric‐specific guidelines, together with limited evidence to guide best practice and limited training in this area. There is a need for guidance and education for the diagnosis and management of paediatric CFS/ME in Australia.